2004
DOI: 10.1590/s0100-879x2004001000017
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial contractility of the isovolumetrically beating isolated rat heart

Abstract: Several indexes of myocardial contractility have been proposed to assess ventricular function in the isovolumetrically beating isolated heart. However, the conclusions reached on the basis of these indexes may be influenced by ventricular geometry rather than contractility itself. The objective of the present study was to assess the performance of widely used contractility indexes in the isovolumetrically beating isolated heart in two experimental models of hypertrophy, the spontaneously hypertensive rat (SHR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
1
2
0
1
Order By: Relevance
“…Later, Sato et al [32] using a miniaturized conductance catheter showed that ESPVR is useful for evaluating myocardial contractility in rats. Other studies in rats submitted to the same experimental model have shown that this index is useful for detecting alterations in myocardial contractility associated with ventricular dilatation [11,33]. In our study, finding an inverse and significant association between ESPVR and dilatation in both the AVF and control group suggests that in isolated rat heart, this index is influenced by ventricular volume, independently of contractile state.…”
Section: Discussionsupporting
confidence: 71%
“…Later, Sato et al [32] using a miniaturized conductance catheter showed that ESPVR is useful for evaluating myocardial contractility in rats. Other studies in rats submitted to the same experimental model have shown that this index is useful for detecting alterations in myocardial contractility associated with ventricular dilatation [11,33]. In our study, finding an inverse and significant association between ESPVR and dilatation in both the AVF and control group suggests that in isolated rat heart, this index is influenced by ventricular volume, independently of contractile state.…”
Section: Discussionsupporting
confidence: 71%
“…Is isovolumic ventricular pressure measured by balloon a reliable surrogate for contractility and does it reflect pumping capacity? This technique for assessing contractility is well established in the physiological literature both in rats, 27 in dogs in our laboratory 28 and elsewhere 20 and in human donor hearts. 17,19 The intraventricular balloon system is easy to set up and this can be done during reperfusion.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Cardiac edema has been described previously during prolonged continuous ex vivo perfusion. 26,27 To set our lactate cutoff, we utilized a lactate of 10 mmol/L multiplied by a factor of 2 over the Hamed cutoff of 5 mmol/L to account for our blood perfusion priming volume of 600-800 mL being approximately half that of the priming volume of the OCS (1200 mL). 18 Although both our DP and lactate cutoffs were somewhat arbitrary, they allowed us to correlate measurements of function and lactate metabolism in individual hearts.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Como demonstrado na literatura (14,15), todos os ventrículos dos animais hipertensos (BHR e SHR) apresentavam um aumento na relação entre o peso ventricular/volume inicial (V 0 ) quando comparados aos ratos normotensos (WST) (WST = 4,73 ± 0,70; BHR = 7,16 ± 2,33*; SHR = 7,96 ± 1,12* mg/ml, *p < 0,05 vs. WST). Quando se compararam esse parâmetro entre ratos normoglicêmicos e diabéticos, verificou-se uma redução desse índice nos ratos BHR + DM e SHR + DM (WST + DM = 5,64 ± 1,06; BHR + DM = .4,79 ± 1,07#, SHR + DM = 4,99 ± 0,95# mg/ml, #p < 0,05 vs. não diabético).…”
Section: Relação Entre O Peso Ventricular/volume Inicial (V 0 )unclassified